Urgensi Pelaksanaan Pemilihan Bupati dan Wakil Bupati Kabupaten Barru ditengah Pendemi Covid-19 - Sri Hardiyanti Lukman (Faculty of Law Andi Sapada Institute of Social Sciences and Business, 2022)
The Corona Virus Disease (COVID-19) outbreak not only has an impact on the public health sector, but also on many other sectors ranging from the economy, education, culture, social, and politics to government. Especially in the political field, the Covid-19 pandemic has caused the 2020 Regional Head Election to be postponed. The government decided to carry out the Regional Head Election in December 2020, by issuing Government Regulation No. 2 of 2020. The steps taken by the government to generate pros and cons among the community, including the organizers, are very rational considering the situation of the spread of Covid-19 which is still increasing. The study in this article uses juridical normative and conceptual methods through a legal approach and tries to examine critically the pattern of the electoral relationship at the center of the pandemic that was hit with the concept of postponing the electoral elections by looking at implications for the development of regional government.